Floristic inventory and structural aspects of the shrub-arboreal stratum in a fragment of the Atlantic Forest in the medium valley of Paraiba do Sul river, Rio de Janeiro, Brazil - Souza, Gilson Roberto de; Peixoto, Ariane Luna; Faria, Maurício Jorge Bueno; Zaú, André Scarambone (SITIENTIBUS série Ciências Biológicas, 2007)
The ARIE Floresta da Cicuta, with 131 ha, located between Serra do Mar and Serra da Mantiqueira (22º33’2"S, 44º05’00"W), at 400–450 m high. The climate is medium-termal (Cwa of Köppen), with an average temperature of 24ºC in February and 17ºC in July, and an average rainfall of 1.370 mm per year. A floristic survey was proceeded using plots of 10 m x 10 m (n=30) comprising 0.3 ha, in the forest interior. 968 individuals were sampled, with DBH e” 2.5 cm, distributed in 46 families, 113 genus and 184 species or morphoespecies. The richest families in species numbers were Myrtaceae, Fabaceae, Rubiaceae, Lauraceae and Euphorbiaceae. Most abundant populations’ species were Actinostemon communis, Senefeldera multiflora, Maprounea guianensis, Moldenhawera polysperma and Astrocaryum aculeatissimum. Euphorbiaceae was the family that accounts for the largest specimen contingent (48.4%). A. communis accounts for 28.7% of specimens found in the area. Species represented by only one specimen was 41.3%. Cicuta forest represents an important and high biodiverse (H’ = 3.66 nats.ind.-1) remnant of Atlantic Forest and the effective protection of this remnant, is essential for its conservation.